One-step SnO2 nanotree-growth - Schoenherr, P; Hesjedal, T (Wiley, 2016)
We present a comparison between Au, TiO2, and self-catalysed growth of SnO2 nanostructures using chemical vapour deposition. TiO2 enables growth of a nanonetwork of SnO2, whereas self-catalysed growth results in nanoclusters. Using Au catalyst, single-crystalline SnO2 nanowire trees can be grown in a one-step process. Two types of trees are identified that differ in size, presence of a catalytic tip, and degree of branching. The growth mechanism of these nanotrees is based on branch-splitting and self-seeding by the catalytic tip, facilitating at least three levels of branching, namely trunk, branch, and leaf.